2020
DOI: 10.3389/fpsyt.2020.00161
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Poor Sleep Quality in Perinatal and Postnatal Women: A Comprehensive Meta-Analysis of Observational Studies

Abstract: Background: Sleep disturbance is common in perinatal and postnatal women, but the epidemiology of sleep problems is highly variable in these populations. This was a metaanalysis that examined the prevalence of poor sleep quality and its correlates among perinatal and postnatal women.Methods: A systematic search of both international and Chinese databases (PubMed, EMBASE, PsycINFO, Web of Science, CNKI, and Wangfang) was performed. Studies with data on sleep quality measured by the Pittsburgh Sleep Quality Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 70 publications
3
59
3
3
Order By: Relevance
“…The heterogeneity of outcomes were assessed using I 2 , with I 2 > 50% as significant heterogeneity ( Higgins et al, 2003 ). Following the recommendation of the Cochrane handbook ( Higgins et al, 2019 ) and other studies ( Li et al, 2020 ; Xu et al, 2020 ; Yang et al, 2020 ), publication bias was assessed using the funnel plots and Begg’s test and Tweedie’s trim-and-fill analysis. All data analyses were 2 tailed, and the significant level was set at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…The heterogeneity of outcomes were assessed using I 2 , with I 2 > 50% as significant heterogeneity ( Higgins et al, 2003 ). Following the recommendation of the Cochrane handbook ( Higgins et al, 2019 ) and other studies ( Li et al, 2020 ; Xu et al, 2020 ; Yang et al, 2020 ), publication bias was assessed using the funnel plots and Begg’s test and Tweedie’s trim-and-fill analysis. All data analyses were 2 tailed, and the significant level was set at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…This theory is primarily based on three lines of reasoning. The first is that sleep loss is both a symptom and frequently cited precipitant of mania unrelated to childbirth [73], while second, acute sleep disruption occurs almost universally in women during the immediate postpartum [74]. Third, neurotransmitters such as dopamine and serotonin are well evidenced to play a role in mood disorders, the systems of which may interact and overlap to also regulate circadian rhythms, including those relating to the sleep/wake cycle and hormone secretion [75,76].…”
Section: Sleep Deprivation/circadian Rhythm Disruptionmentioning
confidence: 99%
“…There are documented decrements in sleep quality after childbirth; postpartum maternal sleep is characterized by fragmented sleep from waking to feed and tend to infants at night which in turn lowers sleep e ciency (the percentage of time spent in actual sleep) and reduces sleep duration [18][19][20]. In a meta-analysis of 28 studies, Yang et al [21] found that the prevalence of poor sleep quality for women during the postpartum period was 67.2% (95% CI [57.6-75.5%]). In the context of poor postpartum sleep quality, Wilson, Lee, and Bei [22] indicated that up to 60% of women experience elevated fatigue.…”
Section: Introductionmentioning
confidence: 99%